2017
DOI: 10.1182/bloodadvances.2017007211
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapeutical strategies in the prevention of acute, vaso-occlusive pain in sickle cell disease: a systematic review

Abstract: Sickle-cell disease (SCD) is characterized by frequent and painful vaso-occlusive crises (VOCs).Various treatments have been evaluated over the years. However, a clear overview is lacking.The objective of this study was to systematically review all pharmacotherapeutical strategies in the prevention of VOCs beyond hydroxyurea. We performed a systematic literature search (MEDLINE, Embase, CENTRAL). Eligible studies were controlled clinical trials evaluating pharmacotherapeutical interventions targeting the reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 76 publications
1
26
0
Order By: Relevance
“…Vascular occlusion is caused by sickle RBCs obstructing blood flow leading to impaired oxygen supply and nutrients to the organs, vascular dysfunction, ischemia/reperfusion injury, inflammation, and end organ damage. 42,115,128 Ischemia/reperfusion injury stimulates mast cell degranulation. 129 VOC pain is associated with ischemia/reperfusion injury in SCD, and we simulated VOClike pain following hypoxia/reoxygenation in sickle mice.…”
mentioning
confidence: 99%
“…Vascular occlusion is caused by sickle RBCs obstructing blood flow leading to impaired oxygen supply and nutrients to the organs, vascular dysfunction, ischemia/reperfusion injury, inflammation, and end organ damage. 42,115,128 Ischemia/reperfusion injury stimulates mast cell degranulation. 129 VOC pain is associated with ischemia/reperfusion injury in SCD, and we simulated VOClike pain following hypoxia/reoxygenation in sickle mice.…”
mentioning
confidence: 99%
“…Thus, it is exciting to see that there are several different agents with disparate mechanisms of action under investigation. 4,89 In particular, newer agents that target the underlying adhesion processes contributing to VOCs have the potential to work in conjunction with current therapies to reduce VOCs and associated morbidity. If these newer agents can also have a protective effect on the endothelial cells and blood vessels, they may also prevent long-term organ dysfunction.…”
Section: Resultsmentioning
confidence: 99%
“…22 A PRISMA NMA checklist can be found in online supplemental appendix A. The SLR approach updated and expanded an earlier published SLR by Sins et al 23 by including non-controlled studies and included additional interventions. Inclusion and exclusion criteria for studies are summarised in table 1.…”
Section: Systematic Literature Reviewsmentioning
confidence: 99%
“…The search strategies were derived from Sins et al 23 and can be found in online supplemental appendix B along with the complete search protocols in online supplemental appendices C and D. As blood transfusion was not included by Sins et al, 23 we conducted a separate search for blood transfusion from inception of databases to 30 August 2018. For non-transfusion studies, the search date was from 1 January 2017 to 21 June 2018 to bridge the findings of Sins et al 23 Results of searches were managed using Endnote and a Microsoft Excel spreadsheet. Two reviewers screened and selected records independently against inclusion and exclusion criteria using titles and abstracts.…”
Section: Open Accessmentioning
confidence: 99%